Throwing the Moral Dice : Ethics and the Problem of Contingency. - Claviez, Thomas; Marchi, Viola; Badiou, Alain; Balibar, Étienne.; Braidotti, Rosi.; Cornell, Drucilla; Gumbrecht, Hans Ulrich; Naas, Michael; Wolfe, Cary.; Žižek, Slavoj (New York : Fordham University Press, 2021)
From deconstruction to feminism to ecological thought, some of today's most influential thinkers consider the challenge that contingent life poses to the broad claims of ethics. In doing so, they reshape the most debated concepts of moral philosophy.
Commonality versus Individuality: An Ethical Dilemma? -- Critique, Power, and the Ethics of Affirmation -- The Promise of Practical Philosophy and Institutional Innovation -- Ethics of Circular Time -- The Road Not Taken: Environmental Ethics, Reciprocity, and Non-Negative Nonagency -- "There Is No World": Living Life in Deconstruction and Theoretical Biology -- Works Cited -- List of Contributors -- Index
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Contingency (Philosophy); Ethics; Ethics; Contingence (Philosophie); Morale; ethics (philosophy); PHILOSOPHY / Ethics & Moral Philosophy; Contingency (Philosophy); Ethics